A stakeholder-centric fuzzy AHP-TOPSIS framework for prioritizing challenges and solutions in the sustainable circular supply chain of electric vehicle batteries - Aishwarya, V. M.; Ekren, Banu Y.; Singh, Tej; Singh, Vedant (Elsevier, 2025)
The worldwide shift to electric mobility has rendered the establishment of sustainable and circular electric vehicle (EV) battery supply chains an immediate imperative. This study proposes a stakeholder-centric, hybrid multi-criteria decision-making framework that incorporates Fuzzy Analytical Hierarchy Process and Fuzzy Technique of Order of Preference by Similarity to Ideal Solution to prioritize challenges and solutions in the EV battery supply chain. Drawing on stakeholder and sustainability theories, the framework evaluates 10 primary challenge domains, 35 sub-challenges, and 14 solution strategies based on insights from six key stakeholder groups: mining and resource extraction, raw material procurement, manufacturing and product development, supply chain and logistics, product management and strategy, and research and development. FAHP results identify environmental resource and lifecycle concerns and supply network robustness and economic stability as the most significant challenge areas. At the sub-criteria level, stakeholders prioritized scarcity and sustainability of vital resources and vulnerabilities in supply chain architecture. FTOPSIS analysis ranks policy framework and compliance and collaborative and stakeholder engagement as the most influential and widely endorsed solution strategies. A foresight-based sensitivity analysis for the year 2040 compares two contrasting future scenarios: a fully developed circular battery ecosystem and another marked by global supply chain volatility and heavy import dependence. Innovation-driven solutions dominate the former, while policy preparedness and economic incentives dominate in the latter. This study offers a novel, transferable framework that aligns stakeholder priorities with circular economy objectives, providing strategic guidance for fostering resilient and sustainable EV battery supply chains across global regions.
Keywords: 3509 Transportation, Logistics and Supply Chains; 46 Information and Computing Sciences; 35 Commerce, Management, Tourism and Services; 12 Responsible Consumption and Production; 7 Affordable and Clean Energy